Gut dysfunction in the critically ill âˆ’ mechanisms and clinical implications - Lauren Hill (Southern African Journal of Critical Care, 2013)
Gastrointestinal dysfunction is a common problem in the critically ill patient, and is commonly observed in the intensive care unit (ICU). It is recognised that a functional gastrointestinal tract is an important factor in the clinical outcome of patients in the ICU. The difficulty in clinical practice has been the lack of an objective or unified definition or understanding of what gastrointestinal dysfunction in the critically ill means. Additionally, gut problems in ICU may often be fairly occult and challenging to classify by degree. Critical illness-associated gut dysfunction is implicated in aetiological processes that drive critical illness, and is further linked to negative nutritional and infectious consequences and poor clinical outcomes. There is currently no complete, unified pathophysiological model of the phenomenon, and cross-disciplinary research opportunities therefore exist both to clarify the mechanisms and to develop treatments.